Feasibility and Acceptability of Game-Based Cortical Priming and Functional Lower Limb Training in a Remotely Supervised Home Setting for Chronic Stroke: A Case Series - Lim, Hyosok; Marjanovic, Nicholas; Luciano, Cristian; Madhavan, Sangeetha (Frontiers in Rehabilitation Sciences, 2022)
Background: Movement-based priming has been increasingly investigated to accelerate the effects of subsequent motor training. The feasibility and acceptability of this approach at home has not been studied. We developed a game-based priming system (DIG-I-PRIMETM) that engages the user in repeated ankle movements using serious games. We aimed to determine the feasibility, acceptability, and preliminary motor benefits of an 8-week remotely supervised telerehabilitation program utilizing game-based movement priming combined with functional lower limb motor training in chronic stroke survivors. Methods: Three individuals with stroke participated in a telerehabilitation program consisting of 20-minutes movement-based priming using the DIG-I-PRIMETM followed by 30-minutes of lower limb motor training focusing on strength and balance. We evaluated feasibility using reported adverse events and compliance, and acceptability by assessing participant perception of the game-based training. Motor gains were assessed using the 10-m walk test and Functional Gait Assessment. Results: All participants completed 24 remotely supervised training sessions without any adverse events. Participants reported high acceptability of the DIG-I-PRIMETM, reflected by high scores on satisfaction, enjoyment, user-friendliness, and challenge aspects of the system. Participants reported overall satisfaction with our program. Post-training changes in the 10-m walk test (0.10-0.31m/s) and Functional Gait Assessment (4-7 points) exceeded the minimal clinically important difference. Conclusion: Our results indicate that a remotely supervised game-based priming and functional lower limb exercise program is feasible and acceptable for stroke survivors to perform at home. Also, improved walking provided preliminary evidence of game-based priming to be beneficial as a telerehabilitation strategy for stroke motor recovery.